Prevalence, genomic characteristics, and pathogenicity of fowl adenovirus 2 in Southern China - Junqin Zhang; Zimin Xie; Yanlin Pan; Zuoxin Chen; Yunzhen Huang; Linlin Li; Jiawen Dong; Yong Xiang; Qi Zhai; Xingying Li; Minhua Sun; Shujian Huang; et al. (Poultry Science, 2024)
ABSTRACT: In recent years, the occurrence of fowl adenovirus 2 (FAdV-2) has been on the rise in China, posing a significant threat to the poultry industry. This study aimed to investigate the epidemiology, phylogenetic relationship, genomic characteristics, and pathogenicity of FAdV-2. The epidemiological analysis revealed the detection of multiple FAdV serotypes, including FAdV-1, FAdV-2, FAdV-3, FAdV-4, FAdV-8a, FAdV-8b, and FAdV-11 serotypes. Among them, FAdV-2 exhibited the highest proportion, accounting for 21.05% (8/38). The complete genomes of these 8 FAdV-2 strains were sequenced. Genetic evolution analysis indicated that these FAdV-2 strains formed a separate branch within the FAdV-D group, sharing 94.60 to 97.90% nucleotide similarity with the reference FAdV-2 and FAdV-11 strains. Notably, the recombination analysis revealed that 5 out of the 8 FAdV-2 strains, exhibited recombination events between FAdV-2 and FAdV-11. The recombination regions involved Hexon, Fiber, ORF19 genes and 3′ end. Furthermore, pathogenicity experiments demonstrated that recombinant FAdV-2 XX strain is capable of inducing mortality rate of 66.70% and causing more severe hepatitis hydropericardium syndrome (HHS) in 6-wk-old specific-pathogen-free chickens. These findings contribute to our understanding of the prevalence, genomic characteristics, and the pathogenicity of FAdV-2, providing foundations for FAdV-2 vaccine development.